Dynamics of Almost Abelian Transcendental Semigroups - Subedi, Bishnu Hari (Journal of Nepal Mathematical Society, 2023)
In this article, we show that the escaping, Julia, and Fatou sets of an almost abelian transcendental semigroup of finite type coincide with escaping, Julia and Fatou sets of their respective cyclic subsemigroups